DOST deploys indigenous weather equipment to country's disaster-prone areas - Marfal, Allan Mauro V.
The article is about the new modern weather instruments installed by DOST in different areas of the country prone to disaster. These instruments are capable of tracking weather disturbances and enable our weather stations to relay a more accurate forecast and warn the public for possible occurrence of a disaster.